Possible Mechanism of Inhibition of Schiff base Complexes on Gazone (Cynadon) and Cucumber (Cucumis satires) - H.A Boshala; F. I. El- meshedy; A.A Maihub; M.M. El-ajaily (Scientific Journal of University of Benghazi, 2026)
The divalent metal ions Mn, Cu and Zn complexes with Schiff base derived from a reaction of salicylaldehyde with L- valine amino acid (L) have been prepared and investigated by using different physicochemical techniques in terms; elemental analysis, molar conductance measurements, infrared, electronic and electron paramagnetic resonance spectroscopies. The elemental analysis exhibited the formation of 1:1 [M: L] ratio. The molar conductance measurements of the complexes indicated the presence of a non-electrolytic nature. The infrared spectral data displayed coordination sites of the free Schiff base toward the metal ions under investigation. The electronic spectral results of Schiff base and its complexes revealed the existence of π-π * (phenyl), n-π* (H-C =N) transitions, and these results suggest that all the complexes are octahedral. The electron paramagnetic resonance spectral data were reported. The free Schiff base, metal ions and their complexes affected on germination of root and shoot lengths of gazone (cynadon) and cucumber seeds (CuCumis satires)